Semantic Field of Parents and Child Relations in Uzbek and English Languages - Xalilova Zarnigor Muhammadjon qizi (Euro Asian Journal Publishing, 2024)
This scientific article presents a comparative analysis of the semantic field of parents and child relations in Uzbek and English languages. By examining the cultural, linguistic, and social factors shaping kinship terminologies, the study aims to deepen our understanding of how language reflects and influences familial relationships. The analysis reveals both similarities and differences in the semantic domains of parents and child relations, shedding light on the cultural values and linguistic features inherent in each language. The findings have implications for cross-cultural communication and provide a foundation for further research in the field of kinship studies
Keywords: semantic field; parents; child relations; Uzbek language